The Transformation of the Character Einar Wegener to A Transgender Woman in the Film ‘The Danish Girl’: A Psychological Point of View - Rusni Podungge; Rosma Kadir; Irmawaty Umar; Andre Niode (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2023)
This present work aimed to determine the process of transforming one’s identity from a man to a woman when one must overcome obstacles in a real-life condition depicted in the film The Danish Girl. It is based on Freud’s theory about the human psychological level, with the addition of Queer Theory in completing this research. This descriptive qualitative research obtained data source from the biographical film The Danish Girl directed by Tom Hopper, released in 2015. The subject studied is limited on the main character analysis, who later became Transgender and changed his name to Lili Elbe. In this case, this research focuses on changing the character of a man to a woman in a film and also the limitation used to examine this study is to pay attention to the psychological point of view by using and applying two theories as an approach to reviewing this research. Thus, based on the data, it was discovered there were 39 scenes of Einar transforming into transgender, of which 27 scenes represented ID, 7 represented EGO and 5 scenes were SUPEREGO. The objective of  this study are expected to enrich issues related to the development of the human psyche. The researcher hoped that the result of this study also could enrich the next researcher’s knowledge about the psychological problem, especially about The Transformation of the Characters Einar Wegener to Transgender Women. In conclusion, Einar's transformation does not necessarily affect what is inside of him, but everything proceeds according to the time before he becomes a Transgender. The research opens up avenues for further exploration and analysis in the field of transgender studies, gender identity, and psychological development. It encourages future researchers to delve deeper into the topic and conduct more comprehensive studies on the representation of transgender individuals in various media forms.